Gatifloxacin hydrochloride confers broad-spectrum antibacterial activity against phytopathogenic bacteria - Huang, Yanxia; Peng, Bin; Li, Chenhui; Wu, Yuqin; Zeng, Zixian; Tariq, Moh; Jiang, Lin; Li, Shun-xiang; Wu, Dousheng (Frontiers in Microbiology, 2024)
Bacterial diseases pose significant threats to agriculture and natural ecosystems, causing substantial crop losses and impacting food security. Until now, there has been a less efficient control strategy against some bacterial diseases such as bacterial wilt, caused by Ralstonia solanacearum. In this study, we screened a library of 57 microorganism-derived small molecule compounds and 1 fully synthetic small molecule compound for their antibacterial activity against R. solanacearum. Gatifloxacin hydrochloride exhibited the best inhibitory effect with an inhibition rate of 95% at 0.0625 mg/L. Further experiments demonstrate that gatifloxacin hydrochloride inhibits R. solanacearum growth in a concentration-dependent manner, with the minimum inhibitory concentration of 0.125 mg/L. Treatment with 0.5 mg/L of gatifloxacin hydrochloride killed more than 95% of bacteria. Gatifloxacin hydrochloride significantly inhibited biofilm formation by R. solanacearum. Gatifloxacin hydrochloride also shows good antibacterial activity against Pseudomonas syringae pv. tomato DC3000 and Xanthomonas campestris pv. vesicatoria. Exogenous application of gatifloxacin hydrochloride suppressed disease development caused by R. solanacearum and P. syringae. In summary, our results demonstrate the great potential of microorganism-derived and synthetic small molecules as broad-spectrum antibacterial compounds, providing alternative ways for the efficient control of bacterial plant diseases.